Liver transplant-facilitated CD161+Vα7.2+ MAIT cell recovery demonstrates clinical benefits in hepatic failure patients - Wei Wang; Chen Dai; Peng Zhu; Mi Wu; Haoquan Zhang; Qing Wei; Ting Zhou; Xiaosheng Tan; Ying Jiang; Xue Cheng; Zhihui Liang; Xiongwen Wu; et al. (Nature Communications)
Abstract Mucosal-associated invariant T (MAIT) cells exert multifaceted effects such as anti-microbial activity, tissue repair, and pro-fibrotic effects across various disease settings. Nonetheless, their role in liver injury and hemostasis remains debated. Here, we report a significant depletion and functional dysregulation of MAIT cells, which is associated with disease severity and accumulated bile acids in HBV-infected patients with varying degree of liver injury. Liver transplantation facilitates a gradual recovery of recipient-originated MAIT cells. Transcriptome analysis reveals enhanced MAIT cell activation, while TCR mining demonstrates clonotype overlap between circulating and hepatic MAIT cells during significant liver injury. TCR-activated MAIT cells from transplant recipients display higher protective capacity but reduced pathological potential than those from liver failure patients. Compromised recovery of MAIT cells is linked to post-transplantation complications, whereas prompt recovery predicates favorable clinical outcome. These findings underscore the intricate interplay between MAIT cells and the hepatic environment, highlighting MAIT cells as potential therapeutic targets and sensitive predictors for clinical outcome in individuals experiencing liver failure and post liver transplantation.